2021
DOI: 10.1002/brb3.2335
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of metformin on cerebral ischemia‐reperfusion injury by regulating PI3K/Akt pathway

Abstract: Metformin (Met) is a commonly used drug in the treatment of type 2 diabetes. Currently, it has been found that Met can effectively reduce the incidence of stroke and exert anti-inflammatory effects. However, its role in ischemia-reperfusion (I/R)induced nerve injury remains unclear. This study aims to investigate the neuroprotective effects of Met in I/R-induced neuron injury as well as the underlying mechanism.A middle cerebral artery occlusion (MCAO) model was established in Sprague Dawley (SD) rats, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…70,71 In addition, metformin has been found to modulate PI3K/AKT activity. 72,73 Enhanced activations of AMPK and PI3K/AKT can amplify autophagy, which aids in the removal of toxic proteins like α -synuclein, thereby preventing dopaminergic neuronal death. 72,73 Finally, animal model studies have found that metformin may induce both angiogenesis and neurogenesis in the brain under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70,71 In addition, metformin has been found to modulate PI3K/AKT activity. 72,73 Enhanced activations of AMPK and PI3K/AKT can amplify autophagy, which aids in the removal of toxic proteins like α -synuclein, thereby preventing dopaminergic neuronal death. 72,73 Finally, animal model studies have found that metformin may induce both angiogenesis and neurogenesis in the brain under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…72,73 Enhanced activations of AMPK and PI3K/AKT can amplify autophagy, which aids in the removal of toxic proteins like 𝛼 -synuclein, thereby preventing dopaminergic neuronal death. 72,73 Finally, animal model studies have found that metformin may induce both angiogenesis and neurogenesis in the brain under different experimental conditions. [74][75][76] In conclusion, the neuroprotective effect of metformin against the PD-R subtype (rapid PD progression) could be attributed to its ability to inhibit neuroinflammation, enhance PI3K/AKT activity for efficient 𝛼synuclein clearance, and stimulate angiogenesis.…”
Section: And Table 2)mentioning
confidence: 99%
“…[40] Studies have confirmed that the PI3K/Akt pathway is progressively inhibited during the pathological injury of cerebral ischemia-reperfusion, and by intervening to trigger and activate this pathway, the trend of excessive apoptosis can be reversed, thus reducing the extent of cerebral ischemia-reperfusion injury. [41] In order to verify the speculation of network pharmacology, this study selected the essential potent substance of MBZD and the core target for molecular docking verification, and the results showed that the critical potent substance of MBZD and the core target protein could bind stably, which verified the prediction of network pharmacology about the mechanism of action of MBZD. However, there are certain limitations to the present study.…”
Section: Discussionmentioning
confidence: 79%
“…The direct inhibition of mTORC1, using pharmacological (sirolimus and everolimus treatment for 6 h after tMCAo induction) and genetic (Raptor-KO mice) approaches, leads to a reduction in pro-inflammatory cytokine expression, in parallel to an increase in the M2 phenotype [ 164 ]. Indeed, recent studies show similar results using different approaches to reduce mTORC1 activity, including the downregulation of some upstream players of the PI3K/mTORC1 pathway [ 165 , 166 , 167 , 168 ]. The mTOR activity regulates the synthesis of pro-inflammatory cytokines ( Figure 6 ) through the mTOR/STAT3 pathway but also enhances autophagy in microglia [ 166 , 169 ].…”
Section: Mtor After Cerebral Ischemiamentioning
confidence: 83%